GAMMA-GLUTAMYL TRANSFERASE (GGT) BLOOD TEST (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The gamma-glutamyl transferase (GGT) test is a test used by blood test providers to diagnose or rule out liver and bile duct diseases. It measures levels of GGT, an enzyme found primarily in your liver that helps protect your cells from damage. Alcohol, drugs, and diseases that affect your liver, pancreas, or heart can cause high GGT levels.